Combined effects of temperature and food concentration on growth and reproduction of Eodiaptomus japonicus (Copepoda: Calanoida) from Lake Biwa (Japan). (22nd June 2015) - Liu, Xin; Beyrend, Delphine; Dur, Gaël; Ban, Syuhei
Summary Life history traits of the freshwater calanoid copepod Eodiaptomus japonicus from Lake Biwa were examined in the laboratory. Four different food concentrations (FC, 103, 5 × 103, 104 and 5 × 104 cells mL−1) and two temperature conditions (15 and 25 °C) were used to clarify the combined effects of those two factors on life history traits. A survival rate of more than 70% was observed at the two medium FCs at 15 °C, although survival was <42% at all six of the other food–temperature combinations. Post‐embryonic development times to adult stage in males and females were affected by both FC and temperature; median development times ranged from 28.7 to 37.3 and 31.4 to 35.0 days at 15 °C and 13.7 to 23.9 and 14.3 to 27.7 days at 25 °C, respectively, for males and females. An interaction between the two experimental factors was found only for females, with food shortage being most acute at 25 °C. Clutch sizes also increased with FC at both temperatures and interaction occurred between those two factors. Egg production rates increased with increasing FC similarly at both temperatures without an interaction effect. Adult body size increased with increasing FC at both temperatures: for example, average female prosome length increased from 0.865 mm to 0.922 mm at 15 °C and from 0.799 mm to 0.904 mm at 25 °C. Somatic and population growth rates calculated from the experimental data increased with FC, but the increase was more important at 25 °C. These responses to FC and temperature suggest that both growth and population dynamics of this copepod might be more influenced by food shortage at temperatures >15 °C. Adult body sizes under food‐limited conditions in this study are at the lower end of the range of those observed in situ, while those predicted from in situ temperatures, assuming non‐limiting food conditions, were always larger than those of natural populations. Therefore, food shortage appears to be the most important factor affecting both growth and reproduction of E. japonicus in Lake Biwa.